Continuous-infusion and outpatient setting: A chance for patients, a challenge for hospital pharmacists. (October 2020) - Perego, Gianluca; Gregis, Francesco; Rossi, Laura; Mazzoleni, Marta; Nozza, Silvia; Nozza, Renata; Gatti, Vincenzo P
The use of continuous-infusion in outpatient setting could be widely used in oncology and haematology care. Many times the lack of data stability about single drug or admixture of drugs, together with patient education and safety, make difficult the transition from inpatient to outpatient setting. Nowadays, this is a big challenge for hospital pharmacists, who must take into consideration the critical issues related to chemical and physical stability, besides microbiological one, in order to ensure high quality preparations and guarantee the safety and quality of care, to protect patients and their health. The aim of this article is to highlight the critical issues concerning the transition from inpatient to outpatient setting, with particular interest regarding chemotherapy protocols, which require preparation with long-term continuous-infusion.